OPTIMASI PANJANG HYDRAULIC FRACTURE PADA RESERVOIR NON-KONVENSIONAL DENGAN METODE UNIFORM CONDUCTIVITY RECTANGULAR FRACTURE - Eriska Eklezia D.S.; Hadziqul Abror (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2020)
Energy needs in the future will continue to grow along with the growth of the population. Renewable and non-renewable energy sources continue to develop with various innovations. However, energy consumption from non-renewable energy such as coal, oil, and natural gas still dominates. Therefore, one of the potential non-renewable energy sources that can be optimized at present is unconventional oil and gas reserves. Unconventional oil and gas are oil and gas that comes from sourcerock, low permeability reservoirs, such as shale oil, shale gas, tight sand gas, coal bed methane, and methane-hydrate. To produce oil and gas from the tight sand gas reservoir, the hydraulic fracture method is a commonly used method. A hydraulic fracture is a well stimulation technique in which rock is fractured by a pressurized liquid. The process involves the high-pressure injection of fracking fluid into the wellbore to create crack in the deep rock formation through which natural gas, petroleum and brine will flow more freely. When the hydraulic pressure is removed from the well, small grains of hydraulic fracturing proppants hold the fracture open. Well log data such as gamma ray log, SP log, density log, resistivity log and so on will be processed and produce shale volume, porosity, permeability, and water saturation. Procced data from well log will be validated by core data. These data will be input into a reservoir model. A hydraulic fracture design will be made in the reservoir model with a certain length, width, and permeability using the uniform conductivity rectangular fracture method. The simulation will continue by using different length fracture design so that the optimum fracture length value is obtained. Keywords: Hydraulic Fracture, Reservoir Modelling, Reservoir Simulation